Evaluation of compatibility and bio-efficacy of insecticide and fungicide combinations on thrips and fusarial wilt of castor: Evaluation of compatibility and bio-efficacy of insecticide and fungicide combinations on thrips and fusarial wilt of castor - M SENTHIL KUMAR; P DURAIMURUGAN; S JAYA PRABHAVATHI; V A SATHIYAMURTHY (Journal of Oilseeds Research, 2023)
Field experiment was conducted during Kharif 2018 -19 at Tapioca and Castor Research Station, Yethapur to evaluate the compatibility and efficacy of six insecticides and three fungicides at recommended concentration against thrips and fusarial wilt of castor. The pooled mean population of thrips was lowest in the treatment Buprofezin 25 SC + Propiconazole 25 EC which recorded 3.25thrips/spike. The highestper cent wilt reduction percent of 91 % was recorded in Acetamiprid 20 SP+ Carbendazim 50 WP followed by Novaluron 10EC + Carbendazim 50 WP which recorded 89.5 % over control.